Impact of Sirtuin Enzymes on the Altered Metabolic Phenotype of Malignantly Transformed Cells - Gaál, Zsuzsanna; Csernoch, László (Frontiers in Oncology, 2020)
Sirtuins compose a unique collection of histone deacetylase enzymes that have a wide variety of enzymatic activities and regulate diverse cell functions such as cellular metabolism, longevity and energy homeostasis, mitochondria function and biogenesis. Impaired sirtuin functions or alterations of their expression levels may result in several pathological conditions and contribute to the altered metabolic phenotype of malignantly transformed cells in a significant manner. In the 21st century, principles of personalized anticancer treatment need to involve not only the evaluation of changes of the genetic material, but also the mapping of epigenetic and metabolic alterations, to both of which the contribution of sirtuin enzymes is fundamental. Since sirtuins are central players in the maintenance of cellular energy and metabolic homeostasis, they are key elements in the development of metabolic transformation of cancer cells referred to as the Warburg effect. Although its most well-known features are enhanced glycolysis and excessive lactate production, Warburg effect has several aspects involving both carbohydrate, lipid, and amino acid metabolism, among which different tumor types have different preferences. Therefore, energy supply of cancer cells can be impaired by growing number of antimetabolite agents, for which appropriate vectors are strongly needed. However, data are controversial about their tumor suppressor or oncogenic properties, the biological effect of sirtuin enzymes strongly depends on the tissue microenvironment (TME) in which they are expressed. Immune cells are regarded as key players of TME. Sirtuins regulate the survival, activation, metabolism, and mitochondrial function of these cells, therefore, they are not only single elements, but key regulators of the network that determines anticancer immunity. Altered metabolism of tumor cells induces changes in the gene expression pattern of cells in TME, due to altered concentrations of metabolite cofactors of epigenetic modifiers including sirtuins. In summary, epigenetic and metabolic alterations in malignant diseases are influenced by sirtuins in a significant manner, and should be treated in a personalized approach. Since they often develop in early stages of cancer, broad examination of these alterations is required at time of the diagnosis in order to provide a personalized combination of distinct therapeutic agents.